Hepatocytes: A key role in liver inflammation - Gong, Jin; Tu, Wei; Liu, Jingmei; Tian, Dean (Frontiers in Immunology, 2023)
Hepatocytes, the major parenchymal cells in the liver, are responsible for a variety of cellular functions including carbohydrate, lipid and protein metabolism, detoxification and immune cell activation to maintain liver homeotasis. Recent studies show hepatocytes play a pivotal role in liver inflammation. After receiving liver insults and inflammatory signals, hepatocytes may undergo organelle damage, and further respond by release mediators that can act in the microenvironment as well as initiate a robust inflammatory response. In this review, we summarize how the hepatic organelle damage link to liver inflammation and introduce numerous hepatocyte-derived pro-inflammatory factors in response to chronic liver injury.